Likuiditas Saham dan Cash Holding in Indonesia - Bambang Sutrisno (Akuntabilitas, 2018)
Prior studies have focused on the determinants of cash holdings. The purpose of this study is to investigate the relationship between cash holding and stock liquidity in Indonesia. This study employs panel data analysis for a sample of 115 manufacturing firms listed on the Indonesia Stock Exchange over the period from 2010 to 2014. This study considers share turnover as the proxy for the stock liquidity. The results show that stock liquidity has a positive and significant effect on cash holding. This finding is in line with Chen et al. (2012), Nyborg and Wang (2013), and Tehrani et al. (2014).